Managing the Environment - Vohra, B.B. (Journal of Soil and Water Conservation, 2022)
The modest gains made by the environmental movement during the fifteen years of its existence leave no room for complacency when viewed in the context of the enormous challenges which lie ahead. There are four major areas of concern in the current environmental situation, i.e. the preservation of the species, the provision of sanitation and drinking water in all human settlements, the control of industrial pollution and the better management of the country’s natural resources of land, water and vegetation. None of these areas offers any cause for satisfaction. It is obvious that with the limited resources available to us, we are not in a position to make a dent on all the problems which face us. It would be wise to be extremely selective in our approach, for first things must come first. The immediate task before the country is to prevent imminent ecological disaster by taking up a 3-point programme as a minimum agenda for survival. In the first place, Wet l fellings which are still taking place all over the country must be brought to an absolute stop so that we do not lose whatever little natural forests are still left to us. Secondly, it must be recognised that the creation of man-made forests through plantations has proved to be too costly and too dilatory to meet the needs of the situation. The only way in which vegetal cover can be restored to denuded lands quickly and cheaply enough is by putting an end to the practice of uncontrolled grazing by excessive numbers of animals so that the forces of natural regeneration may re•assert themselves. Thirdly, the conservation of soil and water through measures like contour bunding, contour trenching, contour terracing and the construction of small storages in all mini-catchments must be taken up on as extensive a scale as possible to help the forces of natural regeneration to assert themselves and to save the country from droughts as well as from floods. Such a programme must be implemented on a war-footing with the cooperation of all political parties.